Farming is a grind. A Górale’s perspective on labour as a local heritage - Małanicz-Przybylska, Maria (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2024)
During my recent ethnographic fieldwork research in Chochołów in the western Podhale region, I got the impression that the work of the Górale was one of the most valuable issues in everyday life. Although my research was about heritage, not directly about work, I decided to follow my interviewee’s voice and look specifically at work. I concluded that work is one of the most important references in the local value system. Not only is hard work valued and held up as a model, but it is also often presented as inherited. Even in 19th-century texts, one can read that Górale worked hard and that work was significant to them. Modern Górale also emphasise that they have diligence in their blood, that it is something setting them apart, and that it has always been so. Drawing on various theories from heritage studies, I aim to demonstrate that labour in the Podhale region can be viewed as a form of cultural heritage. This heritage juggles between the authorised and the unauthorised discourse, between the tangible and the intangible. Above all, it is linked to the production of locality, community, and a sense of uniqueness. It can, therefore, be seen, as Rodney Harrison wanted, as heritage in action.